+0  
 
0
303
3
avatar+278 

Hi, simplify:

 

\(5*3^x-9*3^{x-2} \over 3^x-3^{x-1}\)

 

I really am stuck with this one...please help..

juriemagic  Nov 9, 2017
 #1
avatar+94128 
+2

hi Juriemagic  laugh

This is an unusual question :)

 

\(5*3^x-9*3^{x-2} \over 3^x-3^{x-1}\\ =(5*3^x-9*\frac{3^x}{9})\div(3^x-\frac{3^x}{3})\\ =(5*3^x-3^x)\div(\frac{3*3^x-3^x}{3})\\ =(4*3^x)\div(\frac{2*3^x}{3})\\ =(4*3^x)\times(\frac{3}{2*3^x})\\ =(4)\times(\frac{3}{2})\\ =6\)

Melody  Nov 9, 2017
edited by Melody  Nov 9, 2017
 #2
avatar+278 
+1

Hi Melody,

 

thanx for the reply...can you just explain how the "5" became a "4" please?

juriemagic  Nov 9, 2017
 #3
avatar+92808 
+1

Note, junemagic

 

5 * 3x  -  3x  = 

 

5 * 3x   -   1 * 3x

 

3x  ( 5 - 1) =

 

3x * 4  =

 

4 * 3x

 

 

cool cool cool

CPhill  Nov 9, 2017

5 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.